Collective genius : the art and practice of leading innovation - Hill, Linda A.
"Unleashing the Collective Genius in Your Organization What is the relationship between leadership and innovation? How can some companies innovate again and again-continuously producing products and services that customers want-while most other firms cannot? How do you unleash consistent creativity in those around you? In this important new book, a team of preeminent thinkers-leadership scholar and Harvard Business School professor Linda Hill (Becoming a Manager, Being the Boss), former Pixar technology wizard Greg Brandeau, MIT researcher Emily Truelove, and writer and former executive Kent Lineback (Being the Boss)-reveal what they say is the inextricable yet significant link between leadership and innovation. Based on extensive research at many of the world's top organizations, Collective Genius makes the compelling argument that today's knowledge-intensive global economy demands innovation not just as a competence, but as a much deeper part of the culture of the enterprise. They say the leadership implications of this are profound and result in the difference between those organizations that consistently innovate and those that do not. With vivid real-life voices, rich ethnographic description, and expert guidance from authors who've led innovation and creativity first hand in their own organizations, Collective Genius will expand and deepen our leadership wisdom and competence for a new century. "--